THE EXISTENCE OF THE PORT OF ENDE IN 19TH CENTURY SAILING AND TRADE IN NUSA TENGGARA: EKSISTENSI PELABUHAN ENDE DALAM PELAYARAN DAN PERDAGANGAN ABAD KE -19 DI NUSA TENGGARA - Anita; Hasti Sulaiman (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2021)
This study aims to determine the existence of the port of Ende in shipping and trade in the 19th century in Nusa Tenggara, as well as the commodities traded in Ende in the 19th century in Nusa Tenggara. The research method uses historical research methods (Historical Methods). The historical method is the process of critically examining and analyzing records and relics of the past or imaginative reconstruction based on data obtained by using a process called historiography. research steps, namely Heuristics, verification, interpretation, and historiography. Ende is one of the trade centers that has an important role in trade in Nusa Tenggara, this is of course supported by the port of Ende City. The port is strategically located on the south coast of the island of Flores and overlooks the Savu Sea, which is a good trade route since there were shipping along the coast. The development of Ende's trade became busier and developed rapidly, the port and the growth of Ende City were developing. Commodities traded at that time included sandalwood, horses and slaves. Many Ende people come to various places, especially to Sumba to buy these merchandise.